Purification of Fibroblasts From the Spiral Ganglion - Anacker, Annett; Esser, Karl-Heinz; Lenarz, Thomas; Paasche, Gerrit (Frontiers in Neurology, 2022)
Using cultures of freshly isolated spiral ganglion cells (SGC) is common to investigate the effect of substances on spiral ganglion neurons (SGN) in vitro. As these cultures contain more cell types than just neurons and it might be beneficial to have cochlear fibroblasts available to further investigate approaches to reduce the growth of fibrous tissue around the electrode array after cochlear implantation, we aimed at a purification of fibroblasts from the spiral ganglion in the current study. Subcultivation of the primary SGC culture removed the neurons from the culture and increased the fibroblast to glial cell ratio in the preparations, which was revealed by staining for vimentin, the S100B-protein and the 200 kD neurofilament. Direct immunolabelling for the Thy1-glycoprotein and the p75NGFR enabled fluorescence-based cell sorting. This procedure resulted in a cell culture of cochlear fibroblasts with a purity of more than 99 %. The received fibroblasts can be subcultivated for up to 10 passages before proliferation rates drop. Additionally, 80 % of the cells survived a first attempt of cryopreservation and exhibited a fibroblast specific morphology. Using the described approach provides a purified preparation of cochlear fibroblasts, which can now be used in vitro for further investigations.